Consumers' knowledge on nutritional and medicinal values of tender coconut water among dwellers in Badagry area of Lagos State, Nigeria (2018)
The study evaluated consumers' knowledge on the nutritional and medicinal values of tender coconut water in Badagry Area of Lagos State. Simple random sampling technique was used to select 117 respondents. Data were collected using structured questionnaire on respondents' personal characteristics, source of information, constraints and knowledge on nutritional and medicinal values of coconut water. Data were analysed using descriptive and inferential statistics. The findings of the study revealed that 37.6% of respondents were between 22-31 years, 58.0% were males, 48.7% had tertiary education, friends and relatives (0.86) was the most used source of information by consumers, storage facilities (0.85) was the most severe constraint 53.4% of the respondents had low knowledge of nutritional and medicinal values of tender coconut water. There were significant relationship between constraints (r=0:201, p=0.000), soured of information (r= 0.204, p=0.005) and knowledge of nutritional and medicinal values of coconut water. The study concludes that there was low respondents knowledge on nutritional and medicinal values of tender coconut water. It is therefore recommended that nutritionist and health workers should sensitize people on the nutritional and medicinal values of tender coconut water.